A unified mechanism for proteolysis and autocatalytic activation in the 20S proteasome - Eva M. Huber (Nature Portfolio, 2016)
The proteasome, an essential molecular machine, is a threonine protease, but the evolution and the components of its proteolytic centre are unclear. Here, the authors use structural biology and biochemistry to investigate the role of proteasome active site residues on maturation and activity.